1804-1835 KHARKIV UNIVERSITY’S FACULTY OF MORAL-POLITICAL DEPARTMENT. PART I - Пересада, О. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
In  the  current  article,  the  moral  and  political  department  of  Kharkiv  University  which  was important in the development of political science in Ukraine and the Russian Empire in 1804-1835 is described. Frameworks of the new university structure were determined by the University charter of 1804. In the article was made an attempt to summarize the knowledge about the department of moral and  political  science  from  the  1804-1835.  The  department  of moral  and  political  sciences  of  the University during the period was reviewed, teaching activities of professors and associate professors of the department were also analyzed.